Effect of Gamma Rays on Seed Germination and Seedling Growth of Robinia pseudoacacia - Singh, S.S.; ., Sujata (Indian Journal of Agroforestry, 2020)
Seeds of Robinia pseudoacacia were irradiated with different continuous and fractionated doses of gamma rays (0, 30, 60, 90 and 120 KR) from a Cobalt 60 source to study its effect on germination behaviour, germination value, germination energy index, mortality percentage and other seedling growth parameters. Root growth and its dry matter production has shown highest sensitivity towards different doses of gamma rays and it is followed by germination value. Fractionated doses have been found more effective in reducing the growth and fresh and dry matter production in the seedlings of Robinia pseudoacacia. LD-50 have been calculated for different parameters and a sensitivity spectrum have been made. Maximum mortality have been recorded under the fractionated dose level of 120 KR.